Resurrection of Scolopendra longipes Wood and Scolopendra cubensis Saussure from synonymy with Scolopendra alternans Leach (Chilopoda, Scolopendromorpha, Scolopendridae): an enigmatic species-group needing phylogeographic analysis, with an overview on the origin and distribution of centipedes in the Caribbean region - Mercurio, Randy J. (Zootaxa, 2016)
Resurrection of Scolopendra longipes Wood, 1862, and Scolopendra cubensis Saussure, 1860, from junior synonymy with Scolopendra alternans Leach, 1815, is proposed. A neotype specimen of Scolopendra longipes is designated. Scolopendra longipes has a restricted range from the Dry Tortugas up through the Florida Keys of Monroe County into the mainland Florida counties of Collier and Dade southeast to the Bahamas, while Scolopendra cubensis is endemic to Cuba. Characters distinguishing S. longipes, and S. cubensis from S. alternans are illustrated and compared using digital photography, micrography and morphometric data. It is suggested that what has been considered Scolopendra alternans from southern Florida through the Caribbean and into northern South America is probably an evolving species-group that has undergone major diversification sometime during the Paleocene and early Eocene 65.5–50 million years ago (Ma), mainly due to geographic isolation caused by a combination of plate tectonics and 100,000 year cycles of glaciation/deglaciation.